PENERAPAN MODEL SUPERVISI ARTISTIK UNTUK MENINGKATKAN KREATIVITAS DAN INOVASI PENGAJARAN SD NEGERI KECAMATAN TOHO, KABUPATEN MEMPAWAH - Julian, Emakulata; Waruwu, Marinu; Halida, Halida; Enawaty, Eny (Jurnal Visi Ilmu Pendidikan, 2025)
This study aims to examine the impact of the artistic supervision model on enhancing teaching creativity and innovation in primary schools within the Toho District, Mempawah Regency. The background of this research stems from the low level of teaching creativity observed in the region, which negatively affects student participation and motivation. Using a quasi-experimental design, this study involved 40 teachers divided into experimental and control groups. The experimental group received artistic supervision, while the control group received traditional supervision. Data were collected using pre-test and post-test measures, assessing teaching creativity with the Torrance Test of Creative Thinking (TTCT). The results revealed a significant increase in creativity scores in the experimental group, with a t-statistic of -16.47 and a p-value of 7.95e-05, demonstrating that artistic supervision significantly enhances teaching creativity. In contrast, the control group showed only a modest improvement. This research provides empirical evidence supporting the effectiveness of artistic supervision in fostering creative and innovative teaching approaches, particularly in rural areas. The findings suggest the need for targeted teacher training and increased resources to support creative education methods.